2016
DOI: 10.1136/bmjspcare-2015-001061
|View full text |Cite
|
Sign up to set email alerts
|

Does simulation have a role in palliative medicine specialty training?

Abstract: Simulation training has been adopted by other industries, particularly aviation, for many years. With patient safety on every agenda, more recently there has been considerable interest and investment in its use for the acute medical specialities. Evidence in palliative medicine, for the use of simulation is mainly limited to advanced communication skills but little is described about its use in developing acute clinical skills. This article describes how in the Yorkshire and Humber Deanery a simulation trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Delirium was also addressed in one study, along with pain and nausea 20. One study utilized a technologically advanced mannequin to test PC trainees in the UK on their management of massive hemorrhage, dyspnea, and opioid toxicity 21. The least commonly addressed skill included in simulation experiences was team communication, addressed in only 6% of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium was also addressed in one study, along with pain and nausea 20. One study utilized a technologically advanced mannequin to test PC trainees in the UK on their management of massive hemorrhage, dyspnea, and opioid toxicity 21. The least commonly addressed skill included in simulation experiences was team communication, addressed in only 6% of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transfer of learning and level of fidelity were not strongly correlated when a high-fidelity mannequin was compared to low-fidelity methods in teaching skills such as auscultation, cardiopulmonary resuscitation, and certain surgical techniques 46. In spite of these nuances in terminology, learners have reported that technologically advanced simulation centers contribute to the realism of the experience 21. However, learners also reported that the addition of a human SP to a robotic simulator was what made the experience “realistic, powerful and moving” 47…”
Section: Discussionmentioning
confidence: 99%
“…Palliative medicine trainees are expected to be able to manage and prove competencies in emergencies like anaphylaxis, opioid toxicity and terminal haemorrhage 17. HFS is now used to train and assess palliative medicine trainees in these acute scenarios 18. Simulation allows trainees to refresh and demonstrate competencies for infrequent but important events and is underutilised.…”
Section: Discussionmentioning
confidence: 99%
“…Within palliative medicine, there is emerging use of simulation, although evidence of this more frequently occurs within an adult palliative medicine setting 2–6. Within paediatric palliative medicine (PPM), use of simulation teaching appears more limited, although this has been used in the UK to upskill hospice-based staff 7.…”
Section: Introductionmentioning
confidence: 99%